The Business of Air Quality: Global Markets and Local Stakeholders - Brody, Florian; Herzog, A. Michael; Trajkovikj, Vladimir; Stamboliev, Aleksandar; Batz, Victoria (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
This work investigates the global market for air quality sensors and data representation. We analyzed a comprehensive sample of players in the air quality sensor market and included a representative set of 21 very different organizations in this study. The encompasses entities, from major players like Breezometer to smaller companies focusing on hyperlocal air quality data, such as Airly and AirScape, and non-profit and community-based entities. The primary purposes of these players are to provide data and sensors, promote environmental awareness, support environmental activism projects, and assist community and government initiatives. Air quality is a pressing issue with significant health and economic consequences, including high child mortality rates. This study delves into the challenges posed by air pollution, both globally and locally, with a particular focus on the situation in North Macedonia, whose capital, Skopje, is Europe's most polluted city and consistently exceeds EU air quality limits. The hardware and software solutions market is poised for growth, requiring substantial investment to expand community-oriented air quality efforts. The critical need for global and localized responses to air quality challenges could be addressed through network-economy approaches. A stakeholder network of environmental pioneers, companies, government organizations, and private sensor operators contributes to powerful data sources that track polluters down and analyze specific impacts. Like historical developments like sewers and clean water access, effective air quality management must become integral to our modern world, safeguarding public health and the environment.
Keywords: Air pollution; Global Market vs. Local Market; sustainable development; Community Engagement; Sensor Market Analysis